(untitled) (The Journal of Geography Education in Africa, 2023)
This paper examines the awareness and lived experiences of 28 secondary-level school learners in Namibia to explore their observations and experiences in their local environments. It investigates the factors influencing their ability and/or willingness to make observations. The research employed open-ended, semi-structured interviews and drawings to collect data from Grade 11 learners in five different locations. The data was analysed using interpretative phenomenological analysis and the theme related to exposure to environments is explored. The study draws on theories of place and informal learning, highlighting the role of everyday experiences in shaping individuals’ understanding of their surroundings. All the participants showed that they are aware of what makes the environment in which they live different to others by describing the geographical concepts present in their local environment. However, the findings show that participants’ ability or willingness to make observations can be hindered or reduced by factors such as a lack of interest and familiarity with their local environment and a preoccupied mind. The study highlights the value of understanding learners’ perspectives from their own lifeworlds and sheds light on the contribution of the local environment to geographical awareness.